2019
DOI: 10.5435/jaaos-d-17-00051
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Failed Arthroplasty for Proximal Humerus Fracture

Abstract: A variety of reasons exist for failure of arthroplasty performed for management of proximal humerus fracture. Revision surgery for these failures is complex and has a high likelihood of inferior outcomes compared with primary arthroplasty. Successful management requires consideration of various modes of failure including tuberosity malunion or resorption, rotator cuff deficiency, glenoid arthritis, bone loss, component loosening, stiffness, or infection. Although revision to a reverse shoulder arthroplasty is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
8
0
3
Order By: Relevance
“…The authors identified female sex, a history of instability, and prior hemiarthroplasty as risk factors for intraoperative periprosthetic humerus fracture [41••, 45]. Technical challenges of arthroplasty in a revision setting included loss of tissue planes, bone loss, and, at times, infection [45]. An implant-specific removal device may reduce the risk of intraoperative fracture during this step [41••].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The authors identified female sex, a history of instability, and prior hemiarthroplasty as risk factors for intraoperative periprosthetic humerus fracture [41••, 45]. Technical challenges of arthroplasty in a revision setting included loss of tissue planes, bone loss, and, at times, infection [45]. An implant-specific removal device may reduce the risk of intraoperative fracture during this step [41••].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Algunos de ellos causan una infección de bajo grado, silente y crónica, por lo cual al obtener un cultivo por aspiración debemos esperar hasta 21 días para descartar la formación de Propionibacterium acnes. 11…”
Section: Infeccionesunclassified
“…25 Durante la realización de estas técnicas la incidencia aproximada de fracturas humerales es de 16%, por lo que debemos estar preparados para su manejo. 11 En los casos en que el manto previo de cemento esté bien fijo al húmero, se puede utilizar la técnica «cement within cement», 26 técnica descrita por Wagner, Sperling y Sánchez-Sotelo. En esta técnica se utiliza el manto de cemento del vástago previo, solamente preparándolo con un legrado del mismo, para después poder colocar un vástago corto cementado dentro del mismo.…”
Section: Wwwmedigraphicorgmxunclassified
“…ORIF with the use of locking plates has been implicated in complications such as malreduction, screw cutout, malunion, nonunion, avascular necrosis, and infection, 5 , 10 whereas HA is often associated with tuberosity malunion or resorption, impingement, periprosthetic fractures, loosening, infection, glenoid arthritis and chronic rotator cuff tears. 2 , 11 13 …”
Section: Introductionmentioning
confidence: 99%
“…For most of them RSA seems to be the only solution that can offer an opportunity for improvement in pain and function. 13 26 …”
Section: Introductionmentioning
confidence: 99%